Design and simulation of optically controlled field effect transistors. Issue 1 (9th December 2013) - Sorianello, V.; Colace, L.; Rajamani, S.; Assanto, G.; Cristiano, Fuccio; Pichler, Peter; Tavernier, Clément; Windl, Wolfgang
Abstract Technology roadmaps identify the transmission bottleneck as one of the major challenges at high frequencies and in compact geometries. Increasing bandwidth and massive data processing prompt for the use of optics over short distances, down to board‐to‐board, chip‐to‐chip and even intra‐chip. In this framework, optical to electric converters are key elements. We investigate the feasibility of an optically controlled field effect transistor (FET), a device capable of switching when driven by light (rather than voltage) thanks to a photosensitive gate. We develop a physical model in order to simulate with TCAD the modulation of FET channel conductivity, using drift‐diffusion with optical generation. Current modulation of more than one order of magnitude with 1 µW optical power and time response lower than 100 ps can be achieved. (© 2014 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)